College students’ loneliness and mobile phone addiction: mediating role of mobile phone anthropomorphism and moderating role of interpersonal relationship quality - Wang, Huan; Ji, Mingxin; Tu, Huixin; Qi, Yi; Wu, Siyi; Wang, Xingrui (Frontiers in Psychiatry, 2025)
IntroductionAs mobile phone functions expand and diversify, users develop deep emotional bonds with their devices. This has led to a growing concern about mobile phone addiction, particularly among students in universities. Previous research on mobile phones dependency examined their functional impact on user addiction, with limited exploration of individual psychological mechanisms. Unlike prior research that primarily examines mobile phone addiction as a behavioral issue, this study introduces the concept of mobile phone anthropomorphism as a key psychological mechanism in addiction formation. This study examines the relationship between loneliness and phone addiction among students, focusing on the mediating role of phone personification and the moderating effect of relationship quality.MethodsIn this research, the method of random cluster sampling was used to distribute network link questionnaires to universities across China. Descriptive statistical analysis and tests of mediation and moderation effects were conducted utilizing IBM® SPSS® 27.0, and PROCESS 4.1, respectively. A single-factor Harman’s test was used to assess common method variance, and Pearson’s correlation analysis was employed to explore the relationships between the major variables.Results(1) A remarkable positive association existed between loneliness and smartphone dependency among students. (2) Mobile phone anthropomorphism functions as an intermediary in the link between loneliness and smartphone dependency among students. (3) Interpersonal relationships quality negatively regulate loneliness, mobile phone anthropomorphism, and smartphone dependency.DiscussionThis study offers a fresh perspective on comprehending the psychological characteristics and mobile phone dependence of young people. Loneliness directly contributes to mobile phone addiction and indirectly reinforces dependence through anthropomorphism.When loneliness increases, college students rely more on mobile phones for emotional sustenance and increase unrealistic interactions, thereby facilitating the development of mobile phone addiction. Strong interpersonal relationships mitigate loneliness, reducing both mobile phone anthropomorphism and addiction risk.